Unravelling the druggability and immunological roles of the SOCS-family proteins - Lynch, Dylan M.; Forrester, Beth; Webb, Thomas; Ciulli, Alessio (Frontiers in Immunology, 2024)
The Suppressor of Cytokine Signalling (SOCS) protein family play a critical role in cytokine signalling and regulation of the JAK/STAT pathway with functional consequences to the immune response. Members of this family are implicated in multiple different signalling cascades that drive autoimmune diseases and cancer, through their binding to phosphotyrosine modified proteins as well as ubiquitination activity as part of Cullin5 RING E3 ligases. Here we review the SOCS family members CISH and SOCS1-SOCS7, with a focus on their complex role in immunity. The interactome and signalling network of this protein family is discussed, and the intricate mechanisms through which SOCS proteins alter and manage the immune system are assessed. We offer structural insights into how SOCS proteins engage their interacting partners and native substrates at the protein-protein interaction level. We describe how this knowledge has enabled drug discovery efforts on SOCS proteins to date and propose strategies for therapeutic intervention using small molecules, either via direct inhibition or leveraging their E3 ligase activity for targeted protein degradation.